(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
The article reformulates meaning in psychotherapy as contextual and emerging, giving primacy to practice through re-opening existentialism in the name of post-existentialism. It will be argued that existential psychotherapy has become stuck and is less likely to have the ‘astonishing’ and ‘changing’ essences of existentialism and more likely to be apolitical.